PEMBELAJARAN DARING BERBASIS PROJECT BASED LEARNING PADA MATERI BANGUN DATAR DI MASA PANDEMI COVID-19 - Pratiwi Dwi Warih Sitaresmi; Tuhfatul Janan; Nuryami Nuryami; Ratna Damayanti; Nurhidayati Nurhidayati (LPPM STAI Muhammadiyah Probolinggo, 2022)
There has been a change in the current learning system at all levels of education due to the coronavirus pandemic. This study aims to explore theoretically from bibliographic studies related to project-based learning during the Covid19 pandemic the impact on policies towards home learning activities. A bold learning system based on project-based learning that provides multiple ways to access learning materials for teachers and students. Many online learning platforms and media are available for free. Some free platforms that have been shown to be effective in solving learning difficulties include Google Classroom and Edmodo. There are at least 12 free online learning resource apps that can be used during the Covid19 pandemic, including Learning House, Icando, Desk Kita, Indonesia X, Smart Class, Google for Education, Microsoft Office 365, Quipper, Ruangguru, Zenius, Sekolahmu, and Cisco Webex. Several obstacles to the implementation of immersive learning include limitations of the internet and unfamiliar knowledge among teachers and students about the adoption of e-learning materials. Therefore, more effort is needed to address these issues starting with individuals, families, educational institutions, government providers and services. One learning approach that can be used to maximize daring learning is to adopt a learning project-based approach. This learning model gives students the opportunity to discuss concepts in depth, which can also improve their learning outcomes.